CHARACTERIZATION OF CELLULOSE AND CELLULOSE NITRATE NANOFILMSSE - Elita Carneiro, Mayara; Stygar Lopes, Marina; Franco Baumel de Andrade, Anna Luisa; Nisgoski, Silvana; Inês Bolzon de Muniz, Graciela (Floresta, 2019)
The objective of this work was the characterization of cellulose and cellulose nitrate nanofilms from the mixture of Kraft pulps of Pinus sp. and Eucalyptus sp. bleached. The production of nanocellulose was made by mechanical processing. To obtain the cellulose nitrate, the nitration was carried out in part of the produced nanocellulose. The characterizations were performed by means of scanning electron microscopy, medium infrared spectroscopy, tensile strength and absorption assay. The results demonstrate that there was influence of nitration in the characteristics of the films produced. The nanofilms of cellulose nitrate appear more interesting for the absorption property, indicating the use of this process for uses that require this characteristic.